Oxidative Stress in Diabetic Nephropathy with Early Chronic Kidney Disease - Alejandra Guillermina Miranda-Díaz; Leonardo Pazarín-Villaseñor; Francisco Gerardo Yanowsky-Escatell; Jorge Andrade-Sierra (Journal of Diabetes Research)
The increase in the prevalence of diabetes mellitus (DM) and the secondary kidney damage produces diabetic nephropathy (DN). Early nephropathy is defined as the presence of microalbuminuria (30–300 mg/day), including normal glomerular filtration rate (GFR) or a mildly decreased GFR (60–89 mL/min/1.73 m2), with or without overt nephropathy. The earliest change caused by DN is hyperfiltration with proteinuria. The acceptable excretion rate of albumin in urine is <30 mg/day. Albuminuria represents the excretion of >300 mg/day. Chronic kidney disease (CKD) is characterized by abnormalities in renal function that persist for >3 months with health implications. Alterations in the redox state in DN are caused by the persistent state of hyperglycemia and the increase in advanced glycation end products (AGEs) with ability to affect the renin-angiotensin system and the transforming growth factor-beta (TGF-β), producing chronic inflammation and glomerular and tubular hypertrophy and favoring the appearance of oxidative stress. In DN imbalance between prooxidant/antioxidant processes exists with an increase in reactive oxygen species (ROS). The overproduction of ROS diminishes expression of the antioxidant enzymes (manganese superoxide dismutase, glutathione peroxidase, and catalase). The early detection of CKD secondary to DN and the timely identification of patients would permit decreasing its impact on health.